Elevated Levels of Soluble Axl (sAxl) Regulates Key Angiogenic Molecules to Induce Placental Endothelial Dysfunction and a Preeclampsia-Like Phenotype - Gui, Shunping; Zhou, Shengping; Liu, Min; Zhang, Yanping; Gao, Linbo; Wang, Tao; Zhou, Rong (Frontiers in Physiology, 2021)
Preeclampsia (PE), a severe pregnancy-specific syndrome, is characterized by impaired placental angiogenesis. Although the pathogenesis of this condition remains largely unclear, vascular systemic endothelial injury is thought to be the common contributing factor. Soluble Axl (sAxl), a biomarker of endothelial dysfunction, is known to be abnormally increased in a variety of diseases associated with vascular injury. In a previous study, we found that the plasma levels of sAxl were significantly higher in PE with severe features (sPE) than in pregnant women who did not have PE. The current study aimed to further explore the potential role of sAxl in vascular injury in patients with sPE. We found that the upregulation of sAxl in maternal plasma was positively correlated with the plasma levels of sFlt-1 and negatively correlated with placental NO synthase (eNOS) in women with sPE. Furthermore, elevated levels of sAxl suppressed proliferation and endothelial tube formation and promoted cytotoxicity in human umbilical vein endothelial cells (HUVECs) through the downregulation of p-Akt, p-p70S6K, p-mTOR, and Grb2. Subsequently, we established a pregnant rat model with PE-like characteristics by injecting pregnant rats with an adenovirus expressing sAxl. These rats exhibited a typical PE-like phenotype, including increased blood pressure, proteinuria, and fetal growth restriction, along with abnormal placental and fetal renal morphology. In conclusion, our study demonstrated the role of sAxl in systemic vascular injury through the regulation of the expression of key molecules of angiogenesis and described its potential contribution to the development of sPE.